Triplet state spectroscopy of conjugated polymers studied by pulse radiolysis - Monkman, A. P. (2001)
Using the technique of pulse radiolysis we have elucidated the energies and kinetics of triplet states in soluble luminescent conjugated polymers. Using poly(2-methoxy,5-(2'-ethyl-hexoxy)-p-phenylenevinylene) MEH-PPV as an example we explain this technique and show how it can be used to study the triplet states in conjugated polymers. Triplet energy transfer is used to determine 11Ag-13Bu energy gaps and the kinetics of triplet-triplet absorption yields triplet lifetimes. In the case of MEH-PPV, at concentrations up to 50 mg/l, the triplet decay rate shows no change, indicating self-quenching of triplets is not significant. However, if very high electron beam doses are used, high intra chain triplet concentrations can be generated. In this high concentration regime triplet-triplet annihilation becomes effective, as determined by the onset of delayed fluorescence.